Rethinking the Relation between Power and Space: Relational Geometries in the Turkish Football Industry - Demircioglu, Cemre Yaz; Evren, Yigit (KARE PUBL, 2026)
This paper provides a relational perspective on space and power, by using Yeung's (2005) concepts of relational complementarity and relational specificity as two main forms of power. This perspective brings practice and agency, and the power arising from them, to an analyzable and concrete level within economic geography. Our main intention with this article is not only to present a theoretical discussion but also to empirically engage with the complex structure of a relatively understudied sector, the football industry, to demonstrate the reflections of Yeung's relational geometries. With its peculiar nature that revolves around achievement, prestige, and belonging rather than profit maximization at the club level, football presents a valid case to comprehend how power relations across space can produce different geometries. It displays a multi-actor, multi-scale, and multi-layer structure ranging from local fan groups to global broadcasting and from federations to state mechanisms. Considering the specific economic and social dynamics of football, relational complementarity and specificity between different actors becomes more visible. Taking the economic and spatial transformation of the football industry in Turkey from a historical perspective, this article examines the causes and consequences of the disparities between Istanbul and Anatolian-based football clubs. Notably, the growing economic scale after 1990, accompanied by the increasing influence of media, state, and global capital, has led to fundamental transformations in the relational geometries of Turkish football. Throughout this period, power is reproduced in the spatial context through financial capital as well as actors' interactions and their capacities to access networks.
Keywords: Economic geography; football industry; power; relationality; relational geometries; space; SPORTS; Public Administration